Pengaruh Pendidikan Formal, Pelatihan, dan Intensitas Pertemuan terhadap Kompetensi Penyuluh Pertanian - Oos M Anwas (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2013)
This research aimed to find out: 1) the level of formal education, training intensity, meeting intensity, and competence of extention education agent; and 2) the influence of the level of formal education, training intensity, meeting intensity, and competence of extention education agent to the enhancement of competence of the extention education agent. The research used survey method applied to public service extention education agents in Karawang District and Garut District, West Java. Descriptive and multiple regression analysis were used to proceed the data. The result of descriptive statistic analysis showed that the level of formal education was low, the intensity of meeting among the extention education agents mostly was high, the intensity of attended training was very low, and the competence of extention education agent was also low. The analysis of multiple regression showed that the intensity of meeting among the extention education agents and the intensity of training influenced significantly toward the competency of extention education agents, while the level of in-service formal education followed by public service extension education agents was not significant enough to influence their competency. For that reason the intensity of meeting and training should be enhanced. ABSTRAK Penelitian ini bertujuan untuk mengidentifikasi: 1) tingkat pendidikan formal, intensitas pelatihan, intensitas pertemuan antarpenyuluh, dan kompetensi penyuluh pertanian; dan 2) pengaruh tingkat pendidikan formal, intensitas pelatihan, dan intensitas pertemuan antarpenyuluh terhadap peningkatan kompetensi penyuluh pertanian. Penelitian menggunakan metode survei terhadap penyuluh pertanian Pegawai Negeri Sipil di Kabupaten Karawang dan Kabupaten Garut Provinsi Jawa Barat. Pengolahan data menggunakan analisis deskriftip dan regresi berganda. Hasil analisis dekriptif menunjukkan bahwa tingkat pendidikan formal rendah, intensitas pertemuan antarpenyuluh tinggi, intensitas pelatihan masih sangat rendah, dan kompetensi penyuluh pertanian rendah. Hasil analisis regresi berganda menunjukkan bahwa intensitas pertemuan antarpenyuluh dan intensitas pelatihan berpengaruh signifikan terhadap kompetensi penyuluh pertanian, sedangkan tingkat pendidikan formal yang diikuti penyuluh setelah menjadi penyuluh PNS tidak cukup signifikan berpengaruh dalam membentuk kompetensi penyuluh pertanian. Oleh karena itu, intensitas pertemuan antarpenyuluh dan intensitas pelatihan perlu ditingkatkan.